Transferring modern skills in nursing management from France and Romania - Mańkowska, Mańkowska (Nursing in the 21st Century, 2012)
TRANSFERRING MODERN SKILLS IN NURSING MANAGEMENT FROM FRANCE AND ROMANIAIntroduction. The origin of the project proposal was based on the European Union policies on the vocational education and initiatives such as a “New skills for new jobs”. The basic problem which RENOVA tackles is the lack of the managerial skills in Polish and Romanian educational paths in nursing.The evaluation activities implemented within the project support the idea to join e-learning training solutions with interdisciplinary skills and competences essential in everyday work.Aim. The aim of the research was to evaluate how relevant and efficient are new technologies and training solutions in health sector.Material and methods. There were two stages of evaluation activities during the project realization. The first questionnaire was prepared by Polish and Romanian Partners and implemented in a traditional form after the pilot training in both countries, the second one was prepared by English project Partner and implemented 3 months after the pilot training. During the second part of evaluation the online survey tools were used to create easy to fill in and friendly application for participants.Result. The research shows that there’s lack of training based on e-learning solutions for nurses and midwifes as well as an additional trainings to increase knowledge and skills for professionals in nursing.